Bearing capacity of plate anchors subjected to average and cyclic loads in clays. (1st September 2021) - Cheng, Xinglei; Jiang, Ziqiang; Wang, Piguang; Zhao, Yanbing; Liu, Zhongxian
Abstract: Plate anchors has been widely adopted to provide uplift resistance for offshore floating facilities. The research on the bearing capacity of plate anchors under cyclic loads is still relatively rare compared with the monotonic loads. In the present paper, the bearing capacity of plate anchors under the combination of average and cyclic loads in normal consolidation clays with linearly increasing shear strength is investigated by performing finite element analysis. A more reasonable expression is proposed to determine the cyclic loading factor U c y by modifying the formula suggested by Det Norske Veritas. A global cyclic loading factor U c y ∗ is defined to determine the cyclic anchor resistance considering the difference of average stress level for each soil element around the anchor. The method to determine U c y ∗ by finite element analysis is suggested, and then the U c y ∗ for any given normalized average loads and the equivalent number of cycles is determined. The effects of the embedment depth and inclination angles on U c y ∗ are also investigated by performing a series of numerical simulations. An expression of U c y ∗ associated with normalized average loads and the equivalent number of cycles are proposed based on numerical results, which can provide some reference for the engineering design of plate anchors under cyclic loads. Highlights: The cyclic bearing capacity of plate anchors in normal consolidation clays is investigated. A reasonable expression is proposed to determine the cyclic loading factor for Drammen clay. A global cyclic loading factor of plate anchors is defined and its determination method is introduced. An expression of global cyclic loading factor is proposed to determine the cyclic anchor resistance.